Dinamika Sosial Dan Ekonomi Masyarakat Pesisir Di Kelurahan Leato Utara, Kota Gorontalo - Putalan, Reinal; Azzahra Sudirman, Azisah; Nusi, Fakhrunnisa; Ariany, Septian palma (Journal Of Fisheries Agribusiness, 2024)
This study aims to analyze the social and economic dynamics of coastal communities in Leato Utara Village, Gorontalo City, as a form of community response to environmental and social changes. The study employed a descriptive qualitative approach using participatory observation and semi-structured interviews with key informants, including fishermen, community leaders, and women engaged in household-based economic activities. The findings show that social interactions within the community are shaped by kinship-based social structures, collective solidarity, and informal local institutions. Economically, the community depends heavily on the fishing sector, which is affected by seasonal variations and limited access to technology and markets. Social adaptation and economic diversification are key strategies used to cope with external pressures. This study recommends strengthening local institutions and implementing policies that are responsive to the socio-cultural context of coastal communities